On the importance of wind generated waves in embayments with complex orographic features – A South African case study. (November 2022) - Daniels, Tania; Fearon, Giles; Vilaplana, Ana; Hewitson, Bruce; Rautenbach, Christo
Highlights: The wave climate within False Bay and Table Bay is generated taking into account orographic effects. False Bay and Table Bay require high resolution, spatial varying wind forcing to capture the effects of the complex orography. The waves on the western periphery of False Bay and Table Bay are mainly generated by local spatial varying winds. Abstract: The current study explores the importance of local ocean-atmosphere interactions in modelling wave records in embayments surrounded by significant orographic features and semi-sheltered against swell waves. The numerical code Simulating WAves in the Nearshore (SWAN) was employed for this purpose. False Bay and Table Bay, both located adjacent to the Cape Peninsula in South Africa, were used as case studies due to their geographical location and significance at the southern tip of Africa, their proximity to each other and their surrounding orography. Various combinations of atmospheric forcing were investigated (e.g. various atmospheric forcing horizontal resolutions) to distill the importance of remotely originating swell and locally generated wind waves on both peripheries of False Bay and within Table Bay. Generally, both embayments require high resolution, spatially varying wind forcing to capture the effects of the complex orography. The waves on the western periphery of False Bay and Table Bay are mainly generated by local spatially varying winds, while the waves on the eastern periphery of False Bay are mainly the incoming swell. Results are presented via statistical correlations with measured data, time-series comparisons, wind roses and wave field difference plots.